Определение доминантных факторов сохранности груза на автомобильном транспорте - Olga Yur'evna Smirnova; Kirill Konstantinovich Stoyan (Вестник СибАДИ)
Cargo safety in transportation is the main responsibility of the carrier. The increasing of the cargo safety level during of transportation is directly related to the necessity of considering the factors are influence on the cargo safety, which have a complex and invariant impact. Identification of the most important factors (dominant) in the process of the transportation contributes to rational conduct of and technological actions from the point of view of cargo safety during transportation.